Photoluminescence of Ce3+ ions doped in LiAl5O8 aluminate systems - Nikhare, G N; Gedam, S C; Dhoble, S J (Recent Research in Science and Technology, 2012)
The aluminate phosphors LiAl5O8: Ce was synthesized by combustion synthesis. Photoluminescence (PL) characterization of the phosphors has been reported in this paper. The Photoluminescence (PL) emission spectra of the LiAl5O8: Ce phosphors show strong Ce3+ emission at around 310 nm for the excitation at wavelength of 254 nm wavelength of light due to the 5d→ 4f transition. These phosphors may be useful in scintillation.